Isolamento de bactérias endofíticas e estabelecimento in vitro de diferentes genótipos - Faria, Paulo Roberto (2012)
In micropropagation, plant tissue fragments called explants are isolated aseptically, disinfected and cultured in culture medium. However, oxidation and contamination are the main problems in the initiation of the tissue culture plants. In order to initiate the establishment of in vitro methodologies for selected sugarcane varieties a series of decontaminating treatments were performed in shoot tips with different exposure times and concentrations of sodium hypochlorite, casugamicin, ethanol and mercuric chloride. There were no problems with oxidation in any treatment. The use of reagent concentrations and times tested showed not be phytotoxic. Treatment using longer times of exposure to casugamicin and sodium hypochlorite obtained the lowest levels of contamination by fungi and bacteria. However, bacterial contamination rates were high which indicates the necessity of using new procedures for the decontamination process. It is known that the sugarcane is associated with different endophytic bacteria. In order to better study these endophytic bacteria and their relationship with the host plant, promoted the isolation of bacteria in explants of five different varieties of sugarcane: RB98710, RB34068, RB034130, RB034120 and RB034041 to determinate of morphological and physiological characteristics. The thirteen isolates have diversity for morphological and biochemical staining and are characterized as gram-positive. All of them had a production capacity of plant growth factors, and after antimicrobial susceptibility testing, two antibiotics: Ciprofloxacin and Ceftazidime showed the greatest potential for controlling the growth of the isolates. With microbial contamination controlled, studies were conducted to evaluate the effect of growth regulators on in vitro multiplication of shoot tip culture and its roots in three sugarcane varieties: RB98710, RB034041 and RB034130. We used liquid MS medium containing BAP, KIN, NAA and GA3 in different combinations and concentrations. The results showed that, for the three varieties tested, MS medium with 0.2 mg.L-1 BAP and 0.1 mg L-1 KIN are most suitable for higher production of shoots and that the best rooting results were obtained in semi-solid ½ MS medium with 6% sucrose, 5.0 mg L-1 NAA and 0.2% activated charcoal. The plantlets were acclimatized and survivability under ex vitro conditions was 90%, three weeks after the transfer to the greenhouse.